Structural Behaviour of Shredded Waste Paper Reinforced Concrete Beam - Solahuddin, Azuwa; Fadzil, Mat Yahaya (Penerbit Universiti Malaysia Pahang, 2020)
Cement, sand, coarse aggregate, water and reinforcing bar are the materials to make a reinforced concrete beam. The waste paper has been dumped as waste and causes environmental pollution behind mill or landfill. The industry paper wastage for every year is increasing gradually. More spaces are being needed for landfills, uses energy loss of natural resources and increase of expenditure and various types of pollutions. Utilizing waste paper as an addition in reinforced concrete beam production will reduce environmental pollutions. This research is conducted to investigate the structural behaviour of reinforced concrete beam containing 10% shredded mixed and cardboard waste paper as additions in concrete with three types of reinforcements such as full shear reinforcement with stirrup spacing (SS=100 mm) and reduced shear reinforcements with stirrup spacing (SS=150 mm) and (SS=200 mm). All specimens are subjected to air curing at 28 days. The results of load-deflection behaviour and ultimate load-bearing capacity are better with 10% shredded mixed and cardboard waste paper at 28 days of air curing with full and reduced shear reinforcements. The finding shows that reinforced concrete beam with full and reduced shear reinforcements containing 10% addition of shredded cardboard waste paper in concrete exhibits the highest load at yield (Py), ultimate load (Pu), maximum load (Pmax) representing the load-carrying capacity, load at first crack (P1) and the lowest yield deflection (δy), ultimate deflection (δu), maximum deflection (δmax) compared to 10% SCPWP and 0%. This study indicates that shredded mixed and cardboard waste paper can be used as additional materials in reinforced concrete beam production.